Walter B. Wriston with his daughter, Catherine, in front of the Statue of Liberty (Tufts Archival Research Center, 2008)
3.2 x. 5.1. The print and digital image were created from 'File2814' from the CD titled 'Walter B. Wriston Photographs - CD 1'.